Sex and Gender Differences in Ischemic Heart Disease: Endocrine Vascular Disease Approach (EVA) Study Design - Raparelli, Valeria (J Cardiovasc Transl Res, 2018)
Improvements in ischemic heart disease (IHD) management have been unbalanced between sexes, with coronary microvascular dysfunction considered the likely underlying reason. The Endocrine Vascular disease Approach (EVA) is an observational study (Clinicaltrial.gov NCT02737982) aiming to assess sex and gender interactions between coronary circulation, sexual hormones, and platelet function. Consecutive patients with IHD undergoing coronary angiography will be recruited: (1) to assess sex and gender differences in angiographic reperfusion indexes; (2) to evaluate the effects of estrogen/androgen on sex-related differences in myocardial ischemia; (3) to investigate the platelet biology differences between men and women with IHD; (4) to verify sex- and gender-driven interplay between response to percutaneous coronary intervention, platelets, sex hormones, and myocardial damage at baseline and its impact on 12-month outcomes. The integration of sex and gender in this translational project on IHD will contribute to the identification of new targets for further innovative clinical interventions.